Pengembangan Sistem Rekomendasi Tempat Pembelian Makanan Korea Berbasis Android dengan TOPSIS dan LBS (Studi Kasus: Kota Malang) - Desy Diandra Bestari; Ratih Kartika Dewi; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The existence of Korean food stands in Malang cannot be considered having a small number. Based on the results of a survey on people who have visited Korean restaurants in Malang, half of the participants faced some difficulties when it comes to determining which places they will visit due to many options. Moreover, the names of recommended restaurants emerged from browsing through search engines did not really sit well with the criteria. This study aims to create a recommendation system for Korean food stands based on Android by applying the TOPSIS algorithm and LBS technology. The criteria used in this application consists of price, number of menus, duration of opening hours, number of seats, and location distance. This system will display a list of recommendations of Korean food stands along with the information and locations of the seller in the form of maps. The results of functional validation test using the blackbox testing method obtain 100% valid results for all functional requirements. For the results of testing validation of the algorithm by comparing the results of the system output with manual calculations obtain 100% valid result. Then, average score of usability testing obtain 74,5 which means the application is in acceptable category, C category and good category. Therefore, the result of compatibility testing show application can work well in all of testing devices.